2022
DOI: 10.1002/vro2.37
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a targeted treatment strategy for the sustainable control of Ascaridia galli infections in laying hens

Abstract: Background: Ascaridia galli is a widespread problem in cage-free egg production. Sustainable control of nematode infections is a key component in this sector. This study investigates the effect of a treatment strategy against A. galli, aiming to propose a guideline for anthelmintic use on commercial poultry farms. Methods: A total of eight flocks of laying hens (a-h) from five commercial poultry farms were included in this study. Faecal samples were collected on a biweekly basis starting at 7-13 weeks post-pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Based on the results of the pre-research survey, farmers rarely conduct regular fecal examinations for early detection of digestive tract helminth egg infection. Laying hens infected with helminthiasis and no antihelmintic treatment will cause the development of worms in the host body to continue as the laying hen age so that the EPG value will be higher in older chickens (Tarbiat et al, 2022). Comparison of layer phase age between adult and old hens showed no significant effect on the degree of gastrointestinal tract protozoan infection (P>0.05).…”
Section: Resultsmentioning
confidence: 91%
“…Based on the results of the pre-research survey, farmers rarely conduct regular fecal examinations for early detection of digestive tract helminth egg infection. Laying hens infected with helminthiasis and no antihelmintic treatment will cause the development of worms in the host body to continue as the laying hen age so that the EPG value will be higher in older chickens (Tarbiat et al, 2022). Comparison of layer phase age between adult and old hens showed no significant effect on the degree of gastrointestinal tract protozoan infection (P>0.05).…”
Section: Resultsmentioning
confidence: 91%
“…To date few studies have looked at TT programmes to control A. galli based on non-invasive diagnostics. Three studies using an arbitrary threshold of 200 eggs per gram (EPG) of faeces as a treatment indicator in the TT groups showed a lower worm burden and a lower cumulative number of eggs in the faeces ( Tarbiat et al, 2016b , 2020 , 2022 ). Interestingly, in one of these studies, the hens in the TT group also showed higher egg production as well as better feed conversion and plumage condition compared to the conventionally dewormed groups and the untreated control group ( Tarbiat et al, 2020 ).…”
Section: Targeted Treatmentmentioning
confidence: 99%
“…Such situations lead to cross-resistance and change in gene expression (Von Samson et al 2005). Ascradia galli is completely susceptible to benzimidazoles (Tarbiat 2018) but some selected species of this helminth have shown resistance. Change in β-tubulin genes leads to either the deactivation of receptors or decrease in affinity of receptors to bind with the benzimidazoles (Lubega et al 1990;Keri et al 2015).…”
Section: Reasons For Anthelmintic Resistancementioning
confidence: 99%
“…Resistance is the phenomenon in which parasites are unable to respond to those chemicals that are lethal to them (Von samson et al 2005;Beech et al 2011). Many cases of anthelmintic resistance have been reported from different parts of the world (Giri et al 2015;Tarbiat 2018). Resistance against anthelmintics is common because of the modification in helminths due to frequent exposure of parasites to a particular anthelmintic (Kaplan et al 2012;Whittaker et al 2017).…”
Section: The Demand Of Phytochemicals As Anthelminticmentioning
confidence: 99%